Exploring Collaborative Approaches in Literature Education: Fostering Creative Expression and Student Engagement through Adaptation of â€œAn Inspector Callsâ€ - Jayapalan, Evelyn; Theventhiran, Daviena; Shreevaani, Sadhana; Selvraju, Joycelyn; Seigar, Iveena Sharveeni; Velautham, Anjali (JOLLT Journal of Languages and Language Teaching, 2024)
Encouraging undergraduate students to engage in literary interpretation fosters creative thinking and enables them to perceive contexts in diverse and meaningful ways. Collaborative efforts among students to develop a unified interpretation of a new plot derived from the original storyline can liberate them from rigid thought patterns, allowing for greater expression of creativity in literary appreciation. Â This qualitative study aims to explore the undergraduatesâ€™ creativity and ability through conceptualization and dramatization by demonstrating their appreciation with practical application.This research is a descriptive research employing a qualitative approach. The study involves 14 TESL undergraduates from a Malaysian higher education institution, second and third-year students created a new interpretation of a plot for Part 2 of 'An Inspector Calls,' drawing inspiration from the Freytag Pyramid. This study utilizes content analysis of the new plot structure and an observation checklist for documenting the staging process.. The findings of the study reveal the TESL undergraduates' proficiency in appreciating the essence of "An Inspector Calls" through the successful creation of a compelling plot. Additionally, they demonstrate a comprehensive grasp of literary elements by effectively staging the envisioned plot. The study concludes that TESL undergraduates possess the capability to showcase their literary interpretation and creative expression with practical application, as evidenced by their creation and staging of ACP2." This study implies the importance of incorporating creative activities into the teaching of literature, as it enhances students' creativity and interpretation of literary works. Educators can leverage projects like this to foster students' creativity and practical application in literary interpretation.